Numerical modeling of the morphological change in Lhok Nga, west Banda Aceh, during the 2004 Indian Ocean tsunami : understanding tsunami deposits using a forward modeling method - Li, Linlin (2013)
A coupled hydrostatic and morph-dynamic model COMCOT-SED was used to investigate the morphological change in Lhok Nga bay during the 2004 Indian Ocean tsunami, and the coupled model predicted the thickness of tsunami deposits in agreement with the measured ones. The relationship between the characteristics of tsunami deposit and flow hydrodynamics was discussed in details. Phenomena such as landward thinning in deposit thickness, landward fining in grain size, and fining upwards in grain size are commonly used to identify tsunami deposits and were examined in this case study. We also discussed the effects of sediment supplies and the constraints that can be put on the earthquake parameters using the information derived from tsunami deposits. This study shows that the model presented in this paper is capable of simulating extreme tsunami events (tsunami wave height ~30 m) in a large domain and that forward models of tsunami sediment transport can be a promising tool to help tsunami geologists understand tsunami deposits.